Design of JIB Crane 600 kg Electric Powered - Yahya; Indra Gunawan (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
As it is known that the construction of high-rise buildings requires a tool in the form of a JIB Crane, which is used to transport materials from the bottom to the top. This JIB Crane is installed at the top of the tall building. In this case to design this tool requires welding and also a hook that is able to withstand the load being transported and moved. In this plan, the material must be chosen and also careful calculations for certain parts such as welded joints. In this study, a JIB Crane was designed with an electric drive to carry a load of 600 kg. And based on the calculations obtained, the load supported by the construction of the JIB Crane design is able to withstand the load where the load from the design is greater than the load that occurs.